2014
DOI: 10.1080/17480272.2013.869256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal modification temperature on the mechanical properties, dimensional stability, and biological durability of black spruce (Picea mariana)

Abstract: This study was aimed at evaluating the effect of thermal modification temperature on the mechanical properties, dimensional stability, and biological durability of Picea mariana. The boards were thermally modified at different temperatures 190, 200 and 210°C. The results indicated that the thermal modification of wood caused a significant decrease in the modulus of rupture (MOR) after 190°C, while the modulus of elasticity (MOE) seemed less affected with a slight increase up to 200°C and slight decrease with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
(36 reference statements)
2
8
0
Order By: Relevance
“…MORs tended to decline with increasing treatment time and temperature in a pattern that was consistent with previous studies (Boonstra et al 2007;Ding et al 2011;Lekounougou and Kocaefe 2014); however, the effects were only significant with borontreated samples heated at 200 o C for 4 or 6 h. Interestingly, MOR increased slightly in boron-treated and non-pretreated samples heated for 2 h at 160 o C, but then declined. Similar results were obtained by Kubojima et al (2000), who found that the bending strength increased at the initial stage of the heat treatment and then later decreased.…”
Section: Effects Of Thermal Modification On Morsupporting
confidence: 80%
See 2 more Smart Citations
“…MORs tended to decline with increasing treatment time and temperature in a pattern that was consistent with previous studies (Boonstra et al 2007;Ding et al 2011;Lekounougou and Kocaefe 2014); however, the effects were only significant with borontreated samples heated at 200 o C for 4 or 6 h. Interestingly, MOR increased slightly in boron-treated and non-pretreated samples heated for 2 h at 160 o C, but then declined. Similar results were obtained by Kubojima et al (2000), who found that the bending strength increased at the initial stage of the heat treatment and then later decreased.…”
Section: Effects Of Thermal Modification On Morsupporting
confidence: 80%
“…A number of approaches have emerged for this purpose under the broader title of wood modification including furfurylation (Esteves et al 2011), acetylation (Popescu et al 2014), and thermal treatment (Poncsάk et al 2006;Lekounougou and Kocaefe 2014). Each has merits under certain applications and there is evidence of increasing use of these technologies for wood protection in Europe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(140°C for 90 minutes) to 33.53 N/mm 2 (160°C for 90 minutes). MOR of the samples therefore declined with increasing temperature and time in a pattern that was consistent with the previous studies [17,18,19].…”
Section: Mass Losssupporting
confidence: 90%
“…However, the surface hardness of the heat treated wood can be improved for several wood species thermally modified at treatment temperature lower than 210°C (Sivrikaya et al 2015a). Low temperature and time cause the increase in the hardness value while high temperature and time decrease the hardness value of heattreated wood (Lekounougou and Kocaefe 2014), due to higher degradation of hemicellulose and cellulose and evaporation of extractive compounds (Karamanoglu and Akyıldız 2013;Esteves and Pereira 2009). These last improvements have an adverse effect on wood mechanical properties such as bending and compression strength, stiffness and shear strength (Dilik and Hiziroglu 2012;Candelier et al 2013;Hannouz et al 2015, Hermoso et al 2015.…”
Section: Introductionmentioning
confidence: 99%